ANDROID "STRINGWAN" APPLICATION AS HIGH SCHOOL TEACHING MATERIALS - Viana Maulida; Kaspul Kaspul; Amalia Rezeki (ATRIUM PENDIDIKAN BIOLOGI, 2022)
High school biology concepts require teaching materials that are in accordance with technological developments during a pandemic, especially the concept of tissue structure and function in animals. Teaching materials that are easy to understand, easy to use, interesting, and fun can make it easier for students during the learning process. Android application-based teaching materials are an alternative that is suitable for use in online learning to make it easier for students to understand lessons independently. This study aims to describe the suitability, feasibility, legibility, and response of students to the "Stringwan" teaching material based on the android application for class XI high school students. This study uses a 4D model adapted from Thiagarajan which is carried out until the development stage. The suitability and feasibility test was carried out by experts consisting of two lecturers of the Biology Education Study Program and a partner teacher. The readability test and student responses were carried out by nine students of class XI MIPA 2 SMAN 4 Banjarmasin. The results showed that the suitability of the teaching materials "Stringwan" obtained a score of 4.44 with the "very appropriate" category, the value of the feasibility test results obtained a score of 4.52 in the "very feasible" category, the value of the readability test results obtained a score of 4.36 with the category " very good" and the value of the student response test results obtained a score of 4.22 with the "very positive" category. The score indicates that the teaching materials are suitable for use in the learning process.